HPV Vaccination Rates Amongst Academic Based Gynecology Clinics [1E]. Issue 1 (May 2017) - Jackson-Bey, Tia; Lambert, Tashima; Gamble, Charlotte; Patterson, Latoya; Jones, Monica
Abstract : INTRODUCTION: The Human Papilloma Virus (HPV) vaccine for prevention of cervical cancer is recommended for all females aged 11-26. Inequities exist in vaccination rates, with lower rates of HPV vaccination among minorities and women living in southern states. Within Duke University Medical center, these statistics are unknown. METHODS: This is a retrospective chart review. Data was collected for the month of January 2015 from three Duke based gynecology practices, a resident staffed clinic, and two private Duke affiliated practices. Primary outcome is initiation of HPV vaccination in women aged 11-27. Secondary outcomes include differences in vaccination rates by age, race, ethnicity, practice, and insurance status as well as completion of the vaccination series. RESULTS: There were 254 eligible patients. Of those, 15.7% (n=40) were vaccinated. Insurance coverage was high in this population, 94%. Vaccination rates differed by clinic, ranging from 7.6-23% amongst the three practices with vaccination rate in the resident clinic being the lowest. Hispanic and uninsured women were the least likely to be vaccinated. CONCLUSION: There is an overall low rate of HPV vaccination within gynecology clinics at Duke University. The majority of this population has medical insurance. Barriers to vaccination include Medicaid criteria for coverage of the vaccination. Interventions should be focused on increasing physician knowledge of the need for this effective vaccine, specifically for racial/ethnic minorities as well as lobbying for greater coverage of the vaccination by Medicaid. The study period has been expanded to 1 year to compare these rates over a longer period of time.